Estructuras sub-longutud de onda para el diseño de dispositivos en guía dieléctrica - Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Halir, Robert; Cheben, Pavel; Godoy-Rubio, Rafael; De-Oliva-Rubio, José; Sánchez-Postigo, Alejandro; Luque-González, José Manuel; Sarmiento-Merenguel, Jose Darío; Soler-Penades, Jordi; Nedeljkovic, Milos; Mashanovich, Goran Z.; et al. (Juan Córcoles Ortega et al., 2016)
Sub-wavelength structures are enabling the design of devices based in dielectric waveguides with unprecedented performance in both the near-infrared and mid-infrared wavelength regions. These devices include fiber-to-chip grating couplers with sub-decibel efficiency, waveguide couplers with bandwidths of several hundred nanometers, and low loss suspended waveguides. Here we will report our progress in the electromagnetic modelling and simulation of sub-wavelength structures, providing at the same time an intuitive vision of their fundamental optical properties. Furthermore, we will address design strategies for several integrated optical devices based on these structures, and present the latest experimental results for structures operating both at near and mid-infrared wavelengths.
Keywords: Dieléctricos; guiaondas sub-longitud de onda; guias dielectrica; óptica integrada; Mid-Infrared; silicon photonics